Study of high-temperature thermal stability of max phases in vacuum - Low, It-Meng; Pang, W.; Kennedy, S.; Smith, R. (American Ceramic Society, 2010)
The susceptibility of two MAX phases (Ti2AlN and Ti4AlN3) to high-temperature thermal dissociation in a dynamic environment of high-vacuum has been investigated using in-situ neutron diffraction. In high vacuum, these phases decomposed above 1400C through the sublimation of Ti and Al elements, forming a surface coating of TiN. The kinetics of isothermal phase decomposition was modelled using the Avrami equation and the Avrami exponent (n) of isothermal decomposition of Ti2AlN and Ti4AlN3 was determined to be 0.62 and 0.18 respectively. The characteristics of thermal stability and phase transitions in Ti2AlN and Ti4AlN3 are compared and discussed.